Prevalence of Left Ventricular Dysfunction and Relationship with Serum Selenium in Apparently Healthy Pregnant Women: Results from the PEACE Registry - Kamilu M Karaye (International Cardiovascular Forum Journal, 2020)
Background Peripartum cardiomyopathy (PPCM) is common in North-West Nigeria and many affected patients have selenium deficiency. It is not known whether asymptomatic cardiac dysfunction related to selenium deficiency commonly starts during pregnancy in the region. The study aimed to determine the prevalence of left ventricular (LV) systolic and diastolic dysfunction in apparently healthy pregnant women and if there is relationship with serum selenium, in a society with high prevalence of PPCM. Methods This was a prospective longitudinal study carried out in 3 centres in Kano, Nigeria. 108 apparently healthy pregnant women were consecutively recruited between the 28th and 38th weeks of gestation and re-evaluated at the 6th to 8th weeks postpartum. Serum selenium was measured at enrolment during pregnancy. LV systolic dysfunction was defined as LV ejection fraction (LVEF) below 50% and LV diastolic dysfunction was defined and graded according to the recommendations of the American Society of Echocardiography. Results LV systolic dysfunction and diastolic dysfunction were found in 6 subjects (5.6%) and 20 subjects (18.5%) during pregnancy, and in 9 subjects (10.2%) (p=0.340) and 14 (15.9%) (p=0.631) of them after delivery, respectively. Mean LVEF was 62.2±6.9% and 60.6±8.2% (p=0.108) during pregnancy and after delivery respectively. Mean LV end-diastolic dimension measured during pregnancy (48.6±4.9mm) was not significantly different to what was obtained after delivery (47.2±6.9mm) (P=0.099). Mean left atrial size (37.0±4.8mm Vs 35.2±4.8mm; p<00.1) and mitral septal E/e ratio (8.4±2.8 Vs 1.3±0.5; p<0.001) were higher during pregnancy than after delivery, respectively. Selenium deficiency (<70µg/L) was found in only 2.8% of subjects, and serum selenium did not significantly correlate with indices for LV systolic (LVEF) or diastolic (mitral E/e ratio) functions both during pregnancy and after delivery. Conclusions LV systolic and diastolic dysfunction and selenium deficiency were uncommon during apparently healthy pregnancy and early puerperium, and serum selenium did not correlate with indices for LV function, in a population with high prevalence of PPCM.